Literary Learning with Digital Media in Inclusive Settings : Insights and Results from the DBR-Project 'DigiLi' Focussing on Students' Cooperation - Dannecker, Wiebke; Carell, Leonie; Spieß, Sophie; Ambrosini, Caroline; Ziemen, Kerstin (EDeR. Educational Design Research, 2024)
Following on from existing research results (cf. Dannecker, 2020, p. 82f.; Ziemen, 2018, p. 42ff.), the BMBF-funded DigiLi project pursues the question of to what extent a media-supported learning offering can contribute to realizing an educational goal of cultural participation for all (cf. Kerres, 2013, p. 74). Based on Feuser's core idea that "development-inducing learning through cooperation on the Common Subject Matter” (Feuser, 2013, p. 286, transl. DigiLi) can achieve the goal of participation for all, the DigiLi project investigates a learning arrangement in a composite grade seven/eight at the Inclusive University School of Cologne (IUS) which relates to the discussion of a literary text. Here the data collection focusses on collaborative learning, communication, active collaboration, and cooperative togetherness (cf. Reis et al., 2011; Traub, 2019, p. 138; Dannecker, 2020, p. 82f.), before the digital learning arrangement is examined in form of a web app under field conditions. This paper focuses on investigating the cooperation between students in relation to their engagement with literary texts in the form of iterative data collection cycles and presents the results of the data analysis for discussion.